Comparison of the Effectiveness of Antihypertensive Drugs Captopril 25 mg and Amlodipine 5 mg in Lowering Blood Pressure in Hypertensive Patients - Ichlasul Amal; Sri Marfuati; Rini Istisakinah (International Journal of Health and Pharmaceutical (IJHP), 2025)
Hypertension is a major global health problem with increasing prevalence and significant risks of complications. This study aims to compare the effectiveness of Captopril 25 mg and Amlodipine 5 mg in lowering blood pressure among hypertensive patients. An analytical observational study with a cross-sectional design was conducted at Waruroyom Community Health Center, involving 70 patients divided equally into two groups. Data were collected using structured questionnaires, medication adherence sheets, and calibrated digital blood pressure monitors. Univariate and bivariate analyses were performed, including paired T-tests and Mann-Whitney tests. The results showed that both Captopril and Amlodipine effectively reduced systolic and diastolic blood pressure. However, Amlodipine 5 mg demonstrated a significantly greater reduction in diastolic blood pressure compared to Captopril 25 mg, while both drugs had similar effects on systolic blood pressure. The conclusion is that Amlodipine may be preferred for patients requiring greater diastolic blood pressure control, although both drugs are effective for systolic reduction.